PENERAPAN APLIKASI AUGMENTED REALITY UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MATERI ALAT GERAK MANUSIA KELAS VI SDN SIDOTOPO IV/51 SURABAYA - Afida Sukmaningrum; Vicky Dwi Wicaksono; Sulistyowati; Rizki Nur Rosidah; Endah Dwi Endratmo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is an example of classroom action research that uses an augmented reality application to determine the improvement in learning outcomes of students in class VI human locomotion material. The subjects of this research were 30 students in class VI-A at SDN Sidotopo IV/51 Surabaya. The classroom action research model used is the Kemmis and Tagart model in 2 learning cycles. Each cycle consists of planning, implementation, observation and reflection. The research method used is descriptive qualitative. The data in this research were obtained from written tests from cycle I and cycle II. The results of classroom action research in cycle I showed that learning completeness reached 63.33% and learning completeness in cycle II reached 86.67%. Based on the results of the classroom action research, it can be seen that there was an increase of 23.34%, so it can be stated that there was an increase in student learning outcomes in class VI human locomotion material at SDN Sidotopo IV/51 Surabaya through the application of the augmented reality application.